2021
DOI: 10.1002/jsfa.11383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasound pretreatment on the functional and antioxidant properties of fermented and germinated Lupin protein isolates grafted with glucose

Abstract: BACKGROUND This study examined the functional and antioxidant properties of Maillard reaction (MR) products of lupin protein isolate (LPI), fermented (FLPI), and germinated (GLPI) with glucose (G), treated with ultrasound (US) at different power levels (20–40–60–80%) for 15 min. The MR was conducted in a water bath for 180 min at 90 °C. RESULTS The Trolox‐equivalent antioxidant capacity (TEAC) values were found to be 46.79%, 56.43%, and 35.56% for the control (C), 58.99%, 80.17%, and 69.73% for conjugates of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…Reason of decreased ESI might be due to the short range of the oil–water interface, which resulted from the steric repulsion after the combined treatments of high‐pressure homogenization and ultrasound. Işçimen and Hayta (2022) observed that the EAI and ESI of lupin protein isolates were negatively affected by the MR and ultrasound processes.…”
Section: Functionality Improvement Of Glycated Plant Proteinsmentioning
confidence: 99%
“…Reason of decreased ESI might be due to the short range of the oil–water interface, which resulted from the steric repulsion after the combined treatments of high‐pressure homogenization and ultrasound. Işçimen and Hayta (2022) observed that the EAI and ESI of lupin protein isolates were negatively affected by the MR and ultrasound processes.…”
Section: Functionality Improvement Of Glycated Plant Proteinsmentioning
confidence: 99%